2014
DOI: 10.1080/1369118x.2014.902984
|View full text |Cite
|
Sign up to set email alerts
|

Understanding micro-processes of community building and mutual learning on Twitter: a ‘small data’ approach

Abstract: This article contributes to an emerging field of 'small data' research on Twitter by presenting a case study of how teachers and students at a sixth-form college in the north of England used this social media platform to help construct a 'community of practice' that enabled micro-processes of recognition and mutual learning. Conducted as part of a broader action research project that focused on the 'digital story circle' as a site of, and for, narrative exchange and knowledge production, this study takes the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 41 publications
2
29
0
2
Order By: Relevance
“…Moreover, the case studies pointed out additional aspects that need to be addressed, such as data inconsistencies and poor data quality (O'Leary, 2013a;Halamka, 2014;Mathew et al, 2015). Several studies also reported concerns for potential security and/or privacy issues (Halamka, 2014;Martinez & Walton, 2014;Stephansen & Couldry, 2014;Bettencourt-Silva et al, 2015). Applying proper analytics to the vast amounts of data is the key in gaining value and insights.…”
Section: Content Analysis Of the Case Study Papersmentioning
confidence: 99%
“…Moreover, the case studies pointed out additional aspects that need to be addressed, such as data inconsistencies and poor data quality (O'Leary, 2013a;Halamka, 2014;Mathew et al, 2015). Several studies also reported concerns for potential security and/or privacy issues (Halamka, 2014;Martinez & Walton, 2014;Stephansen & Couldry, 2014;Bettencourt-Silva et al, 2015). Applying proper analytics to the vast amounts of data is the key in gaining value and insights.…”
Section: Content Analysis Of the Case Study Papersmentioning
confidence: 99%
“…This paper is available at: http://www.journalcbi.co m/architectural-theoryof-innovationexplicating-designnetworks-andmicroprocesses.html mounting scholarly concern that particular microprocesses are not well understood (Fligstein & McAdam, 2012;Lok & Rond, 2013;McPherson & Sauder, 2013;Stephansen & Couldry, 2014).…”
Section: Wwwjournalcbicom Issn 2351 -6186mentioning
confidence: 99%
“…Big data approaches to social media uses hold great promise, although they have been criticized for resting on a 'mythology' that more data is always better and leads to new knowledge and higher accuracy [2]. This has provoked some researchers to define their work as "small data" studies [14], where the focus is on smaller sets of data from social media, often in conjunction with interviews or some form of qualitative content or linguistic analysis.…”
Section: Introductionmentioning
confidence: 98%